Peningkatan kemampuan berbahasa inggris pemuda Riau melalui IELTS Preparation Workshop - Afrianto Daud; Ando Fahda Aulia; Novitri Novitri; Mirza Hardian; Nita Rimayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Today's youth face challenges and competition in life that is more complex than in previous times because the world is getting smaller due to globalization. The problem is that many youths do not yet have sufficient skills to exist in this rapidly changing era. This paper describes a community service activity sponsored by a group of lecturers in the English Education and Communication Studies Study Programs of Universitas Riau which aims to develop the ability of Riau youth to take the international standardised English test (IETLS). This paper further explains the concept of training, the content of the training materials, and the effectiveness of the training. This training lasts for one month with four face-to-face training sessions. The rest is done online through the Google Classroom platform. The content of the training material focuses on improving the ability to take international standardized tests (IELTS). Data from the self-assessment conducted at the end of the service activity session showed that in general this activity had been running well and effectively. The training activities provided positive benefits for the participants as seen from the average self-assessment data in the very good category (3.52). More specifically, the average increase in participants' listening skills after the training was in the very good category (3.43). The speaking ability of the trainees has increased and is in the very good category (3.54). This increase also applies to reading and writing skills in the same category (3.63 and 3.47, respectively). Thus, this training has benefited the trainees in developing their soft skills.